2015
DOI: 10.1597/14-132
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Severity, Midfacial Growth, and Speech Outcomes in Van der Woude/Popliteal Pterygium Syndromes Compared to Nonsyndromic Cleft Lip/Palate

Abstract: Patients with VWS/PPS have more severe forms of labiopalatal clefting and higher incidences of midfacial retrusion, palatal fistula, and velopharyngeal insufficiency following primary repair as compared with nonsyndromic CL/P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
3
7
2
Order By: Relevance
“…As with our study, the participants with VdW syndrome were significantly more likely to require secondary surgery for VPI than the nonsyndromic group. Reardon et al (2015) also found the VdW group had a significantly higher fistula rate but this was not replicated in our study.…”
Section: Comparison With Other "Sommerlad Technique" Studiescontrasting
confidence: 86%
See 1 more Smart Citation
“…As with our study, the participants with VdW syndrome were significantly more likely to require secondary surgery for VPI than the nonsyndromic group. Reardon et al (2015) also found the VdW group had a significantly higher fistula rate but this was not replicated in our study.…”
Section: Comparison With Other "Sommerlad Technique" Studiescontrasting
confidence: 86%
“…Reardon et al (2015) compared patients with VdW and nonsyndromic iCP and Kitchin et al (2019) compared VdW with nonsyndromic CP±L. As with our study, the participants with VdW syndrome were significantly more likely to require secondary surgery for VPI than the nonsyndromic group.…”
Section: Discussionsupporting
confidence: 65%
“…While there have been prior studies investigating paramedian lip pits, dental features, facial features, family histories of VWS, and even wound healing in patients with VWS, the longterm outcome of these patients is not as well reported 13,15,17,20,22,[24][25][26][27][28][29] . Recently, Reardon et al 30 documented a unique study involving the clinical characteristics and surgical course of 28 patients with VWS/Popliteal Pterygium Syndrome (PPS) at one tertiary care center. While the study by Reardon et al (2015) is notable, it does not trace patient speech pathology outside of the need for secondary velopharyngeal repair.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Reardon et al 30 documented a unique study involving the clinical characteristics and surgical course of 28 patients with VWS/Popliteal Pterygium Syndrome (PPS) at one tertiary care center. While the study by Reardon et al (2015) is notable, it does not trace patient speech pathology outside of the need for secondary velopharyngeal repair. We therefore aim to investigate patients with VWS at our institution with an increased focus on speech pathology, specifically resonance, intelligibility, and need for speech therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This bilateral distribution is even more heavily skewed than in the other common cleft syndromes. In van der Woude, 46% have bilateral clefts (Rearden et al, 2015); in CHARGE, 37% have bilateral clefts (Isaac et al, 2018). A phenotypic subgroup analysis has not been reported for Trisomy 13.…”
Section: Discussionmentioning
confidence: 99%